EXPLORING THE POTENTIAL OF GEOGRAPHIC INFORMATION SYSTEM (GIS) APPLICATION FOR UNDERSTANDING SPATIAL DISTRIBUTION OF VIOLENT CRIME RELATED TO UNITED NATIONS SUSTAINABLE DEVELOPMENT GOAL-16 (SDG-16) - Azizul, Ahmad; Tarmiji, Masron; Asykal Syakinah, Mohd Ali; Mohamad Hardyman, Barawi; Zaimuariffudin Shukri, Nordin; Abg Izhar, Bin Abang Ahmad; Mohd Sofian, Redzuan; Luqman Haqim, Bismelah (UMT Press, 2024)
The achievement of Sustainable Development Goal (SDG) 16, which promotes peace, justice, and strong institutions, is significantly hindered by the prevalence of violent crime, particularly gang violence and interpersonal violence, a situation that is especially acute in resource-limited developing nations. This study investigates the application of Geographic Information Systems (GIS) as a strategic tool to bolster the efforts of the Royal Malaysia Police (RMP) and local authorities (PBT) in Selangor, Kuala Lumpur (KLFT), and Putrajaya (WFT), Malaysia, in their fight against violent crime. This research meticulously maps crime hotspots and analyses the interplay between crime incidence and enabling a data-informed approach to crime prevention. Moreover, it evaluates the challenges developing nations encounter in harnessing such technological advancements, focusing on potential collaborations with private entities like Google and Alibaba to enhance the efficacy of GIS technologies in realising SDG-16. This research is expected to reveal the significant potential of GIS in identifying crime hotspots and delineate the obstacles developing countries face in adopting technology. By highlighting the constructive role of private-sector partnerships in fostering these advancements, the research contributes to SDG-16’s objective of building peace, justice, and strong institutions, thereby supporting the overall sustainable development agenda.